The health of Mexicans living in localities with less than 100 000 inhabitants - Juan Rivera-Dommarco; Teresa Shamah-Levy; Tonatiuh Barrientos-Gutiérrez; Sergio Bautista-Arredondo; Martín Romero-Martínez; Blanca Pelcastre-Villafuerte; Pilar Torres-Pereda (Instituto Nacional de Salud Pública, 2019)
Objective. To describe the health and nutritional status of Mexican population living in localities under 100 000 inhabitants (100k) in year 2018 in comparison it with a sample of similar characteristics in 2012. Materials and methods. The more relevant results analyzed in 19 articles about health and nutrition of the population are presented. This included information on access and utilization of health services, health and nutrition status by age groups and households affected by food insecurity (FI). Results. Information was obtained about the health and nutrition status of the population from <100k localities, which is characterized by its higher poverty levels. Conclusions. Great inequities prevails the health and nutrition conditions of the Mexican population. The findings are useful for the devel- opment of public policies capable of reducing health inequities conditions, in order to achieve social equity.